EPIGRAPHIC MONUMENTS AS SOURCES ON THE HISTORY OF THE KELEB GATHER IN THE XV-XVIII CENTURY - Hapizov, Sahban Magomedovic; Sehmagomedov, Magomed Gadzievic (History, Archeology and Ethnography of the Caucasus, 2016)
The article deals with the study of epigraphic monuments of Keleb Gorge (now the southern part of Shamilsky district of Dagestan). They are important sources of anthroponomy because epitaphs contain mainly original personal names which during the process of deepening of Islamization of the population gave way to the Arabic anthroponyms. Epigraphy of the 15th – 16th centuries is often theonly source that characterizes the process of Islamization of the region. The inscriptions also provide important information about the socio-political situation in Mountainous Dagestan in the 17th - 18thcenturies.
Keywords: Keleb; epigraphy; anthroponymy; Islamization; Avar Khanate; synoecism